Perlindungan Hukum atas Kerugian Nasabah Asuransi Terhadap Kasus Gagal Bayar Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Wafa Nurul Inayah; Marsitiningsih marsitiningsih (Kosmik Hukum, 2021)
Legal protection for insurance policyholders is essential because it is associated with standard agreements in insurance agreements. In essence, since the signing of the insurance policy, the insured has received less legal protection because the content or format of the agreement is more beneficial to the insurance company. The unequal position between insurance policyholders and insurance companies and the application of standard agreements causes the function of legal protection for insurance policyholders to be questioned. This study discusses how the legal protection for insurance customer losses against default cases in terms of Law Number 8 of 1999 concerning Consumer Protection and the obstacles in legal protection for insurance customer losses against default cases in Law Number 8 of 1999 About Consumer Protection. The method used in this research is the normative juridical method carried out through a literature study that examines secondary data. Insurance customers, in this case, are consumers who use insurance services which, in carrying out their activities, have the right to obtain legal protection from anything that will harm the consumer. Law Number 8 of 1999 concerning Consumer Protection has clearly stated the legal protection provided for consumers using services or insurance customers, namely by making every effort to achieve legal protection for customers.Keywords: Legal Protection, Insurance, Default